Clinical mitochondrial genetics. Issue 6 (1st June 1999) - Chinnery, Patrick F; Howell, Neil; Andrews, Richard M; Turnbull, Douglass M
Abstract : The last decade has been an age of enlightenment as far as mitochondrial pathology is concerned. Well established nuclear genetic diseases, such as Friedreich's ataxia, 1 2 Wilson disease, 3 and autosomal recessive hereditary spastic paraplegia, 4 have been shown to have a mitochondrial basis, and we are just starting to unravel the complex nuclear genetic disorders which directly cause mitochondrial dysfunction (table 1 ). However, in addition to the 3 billion base pair nuclear genome, each human cell typically contains thousands of copies of a small, 16.5 kb circular molecule of double stranded DNA (fig 1 ). Mitochondrial DNA (mtDNA) accounts for only 1% of the total cellular nucleic acid content. It encodes for 13 polypeptides which are essential for aerobic metabolism and defects of the mitochondrial genome are an important cause of human disease. 92 93 Since the characterisation of the first pathogenic mtDNA defects in 1988, 5 13 over 50 point mutations and well over 100 rearrangements of the mitochondrial genome have been associated with human disease 94 95 (http://www.gen.emory.edu/mitomap.html ). These disorders form the focus of this article.